2021
DOI: 10.1017/s204579602100007x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially preventable hospitalisations for physical health conditions in community mental health service users: a population-wide linkage study

Abstract: Aims Mental health (MH) service users have increased prevalence of chronic physical conditions such as cardio-respiratory diseases and diabetes. Potentially Preventable Hospitalisations (PPH) for physical health conditions are an indicator of health service access, integration and effectiveness, and are elevated in long term studies of people with MH conditions. We aimed to examine whether PPH rates were elevated in MH service users over a 12-month follow-up period more suitable for routine health indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Even before the pandemic, there has been considerable evidence, particularly from low and middle income countries, which has already indicated the heightened morbidity and mortality associated with SMI due to various infectious diseases [8][9][10]. Alongside this, studies in high-income settings have shown that infectious diseases are more prevalent in people with SMI [11][12][13], and have been the leading cause of preventable hospitalisations in this population even prior to the pandemic [14]. Until recently, however, this topic has received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the pandemic, there has been considerable evidence, particularly from low and middle income countries, which has already indicated the heightened morbidity and mortality associated with SMI due to various infectious diseases [8][9][10]. Alongside this, studies in high-income settings have shown that infectious diseases are more prevalent in people with SMI [11][12][13], and have been the leading cause of preventable hospitalisations in this population even prior to the pandemic [14]. Until recently, however, this topic has received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors increase the risk of early death for people living with severe mental illness due to the impact of COVID-19. These include reduced access to healthcare, increased risk of delayed (or missed) diagnosis, lower rates of vaccination [ 11 , 12 ], medication side effects, high rates of smoking [ 13 ], and, crucially, the presence of multiple long-term chronic health conditions [ 3 ]. Older people with mental illness are particularly at risk, given the vulnerability related to aging and the high rates of physical health comorbidity in older people with mental illness [ 2 ].…”
Section: Increasing Disparities In Health Service Accessmentioning
confidence: 99%
“…The existing data indicate that people living with mental illness have much lower hepatitis and flu vaccination rates than the general population [ 27 ]. The low vaccination rates for people with mental illness are unmistakably evident in the five times higher rate of vaccine-preventable hospitalization and seven times higher rate of vaccine-preventable hospital bed days [ 12 ]. People with mental illness are more susceptible to infections during epidemics.…”
Section: Increasing Disparities In Health Service Accessmentioning
confidence: 99%
“…The economic and societal benefits are well established. For instance, national vaccination programs keep people out of hospital, save money and prevent deaths (although there are still opportunities to enhance the effectiveness of vaccination programs by reaching disadvantaged groups and groups with chronic health conditions) 10 . Given this, one must ask: Why is progress in this area so slow?…”
Section: But We Invest Little In Prevention and Early Interventionmentioning
confidence: 99%
“…For instance, national vaccination programs keep people out of hospital, save money and prevent deaths (although there are still opportunities to enhance the effectiveness of vaccination programs by reaching disadvantaged groups and groups with chronic health conditions). 10 Given this, one must ask: Why is progress in this area so slow? There are a least 4 fundamental reasons: philosophical, economic, political and our diffuse, federated leadership structures.…”
Section: But We Invest Little In Prevention and Early Interventionmentioning
confidence: 99%